South Korea HD Hyundai machinery used in West Bank demolitions - Amnesty International (Amnesty International, 2025)
HD Hyundai machinery has been widely used in demolitions of Palestinian-owned structures in the Occupied Palestinian Territory (OPT), according to new visual and testimonial evidence documented by Amnesty International Korea and local human rights groups.
Palestine (Permanent Observer to the United Nations)